The Determinants of Profit Efficiency of Islamic Banks Using Stochastic Frontier Analysis Approach - Hadhek, Zouhaier; Frifita, Manel; Lafi, Mosbah (International Journal of Economics and Financial Issues, 2018)
In this article, we estimate the determinants of the profit efficiency of Islamic banks using the Stochastic Frontier Analysis (SFA) stochastic frontier approach. We use 37 Islamic banks in fifteen countries between 2005 and 2014. We compare efficiency between Islamic banks. In addition, we examine internal (bank-specific) and external variables that can explain sources of inefficiency and those that allow us to reduce profit efficiency scores on a specific number of variables (GDP per capita, average annual inflation rate, population density, size, capital adequacy ratio, financial profitability ratio, credit risk, operational costs). Thus, only credit risk is not a determinant of the efficiency-profit of Islamic banks. Keywords: Islamic banks, Stochastic Frontier Analysis, Profit efficiency, Determinants of profit efficiency. JEL Classification: G2 DOI: https://doi.org/10.32479/ijefi.6996